The Effects of Statins Unrelated to Cholesterol level on Clinical Outcome of Continuous Ambulatory Peritoneal Dialysis Patients - Sug kyun Shin; Yong kyu Lee; Young-Il Jo; Tae ik Chang (The Korean Society of Nephrology, 2012)
Patients who are on CAPD (Continuous Ambulatory Peritoneal Dialysis) show higher serum LDL cholesterol and Triglyceride compared to patients who are on hemodialysis. But higher cholesterol level does not seem to effect on raising mortality or cardiovascular morbidity and CAPD failure. On the contrary, lower serum cholesterol level in CAPD patients tends to raise mortality and morbidity due to poor nutritional status. Methods: This study is a retrospective study designed to evaluate the effect of cholesterol level, statin on CAPD outcome and mortality. Patients who were on peritoneal dialysis for at least 6 months since March 1st, 2000 were included. A total of 467 patients were enrolled in this study. Patients' biological parameter, biochemical parameter and morbidity/mortality during CAPD maintenance period were collected. Results: Patients whose initial cholesterol level were above 240 mg/dL shows significantly low CAPD failure rate compared to patients whose initial cholesterol level were below 200 mg/dL (OR=0.469, p=0.049). Patients whose average LDL-cholesterol during CAPD period were over 100mg/dL showed significantly higher mortality compared to patients whose initial LDL-cholesterol level were below 100mg/dL (OR=1.848, p=0.024). Patients whose compliance to statin during CAPD period was over 80% showed significantly low mortality compared to patients who did not take statin during CAPD period (OD=0.556, p=0.020). Patients showed no significant difference in motality due to total cholesterol, HDL cholesterol levels and patients showed no significant difference in CAPD failure due to HDL/LDL cholesterol, statin usage. Conclusions: Usually compared to HD or CKD patients, serum total cholesterol level in CAPD patients was lower significantly. However, triglyceride level in CAPD patients was significantly higher than CKD or HD patient. In this study, the use of statins unrelated to cholesterol level was significantly effective to clinical outcomes in CAPD patients. To verify this results the larger size and prospective study is needed.